Determinants for cardiovascular disease health check questionnaire: a validation study - Cheong, Ai Theng; Chinna, Karuthan; Khoo, Ee Ming; Liew, Su May (Public Library of Science, 2017)
Background: To improve individuals’ participation in cardiovascular disease (CVD) screening, it is neces- sary to understand factors that influence their intention to undergo health checks. This study aimed to develop and validate an instrument that assess determinants that influence individ- uals’ intention to undergo CVD health checks. Methods: The concepts and items were developed based on findings from our prior exploratory quali- tative study on factors influencing individuals’ intention to undergo CVD health checks. Con- tent validity of the questionnaire was assessed by a panel of six experts and the item-level content validity index (I-CVI) was determined. After pretesting the questionnaire was pilot tested to check reliability of the items. Exploratory factor analysis was used to test for dimensionality using a sample of 240 participants. Results: The finalized questionnaire consists of 36 items, covering nine concepts. The I-CVI for all items was satisfactory with values ranging from 0.83 to 1.00. The exploratory factor analysis showed that the number of factors extracted was consistent with the theoretical concepts. Correlations values between items ranged from 0.30 to 0.85 and all the factor loadings were more than 0.40, indicating satisfactory structural validity. All concepts showed good internal consistency, Cronbach’s alpha values ranged 0.66–0.85. Conclusions: The determinants for CVD health check questionnaire has good content and structural valid- ity, and its reliability was established. It can be used to assess determinants influencing indi- viduals’ intention to undergo CVD health checks.